The Role of Guidance and Counseling Teachers in Addressing Juvenile Delinquency: A Literature Review - Lianingsih, Nestia; Lestari, Mugi (Research Collaboration Community (Rescollacom), 2025)
Juvenile delinquency is an increasingly worrying phenomenon in various countries, including Indonesia. This study aims to explore the role of Guidance and Counseling (BK) Teachers in overcoming juvenile delinquency through a literature review method. This study analyzes prevention strategies, reactive approaches, and curative efforts carried out by BK teachers to deal with deviant behavior committed by adolescents. The results of the study indicate that BK teachers have a key role in preventing and overcoming juvenile delinquency through various approaches, including providing information, group guidance, mediation, home visits, and individual and group counseling. However, the implementation of these strategies often faces internal, external, and institutional obstacles, such as students' lack of confidence to open up, minimal parental attention, and limited school resources. This study emphasizes the importance of a collaborative approach involving teachers, parents, and the community in dealing with juvenile delinquency in a comprehensive and sustainable manner